(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the author considers the comparative analysis of the law and experience of food security in the United States, as well as ways of improving the legislation of the Republic of Kazakhstan in the field. Key words: nutrition, food security, agriculture.